TINGGALAN ARKEOLOGIS SITUS BENTENG RONGI DI KECAMATAN SAMPOLAWA - Asma Asma; Syahrun Syahrun (Laboratorium Jurusan Arkeologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2018)
his study aims to determine the types of remains found on the site of the rongi fortress and how the function of the rongi fort is for the buton sultanate based on its remains. This study uses spatial archeology theory andsettlement approaches. This study uses data collection techniques as a literature study that collects literature relatedto the title of research, observation, documentation, and interviews. Then the stage of data processing and dataanalysis is using contextual analysis.The results of the study showed that the archeological remains were found inthe form of baruga, old house, cannons, weapons, kususuli, tombs, ceramic fragments and pottery fragments. Thefunction of the fort rongi for the buton sultanate based on its archeological remains which functions as a fortress aswell as a settlement.